Analisa Manajemen Portofolio Investasi Reksadana Syari’ah Ditinjau Dari Strategi Investasi Berdasarkan Resiko Investasi Dan Pengukuran Kinerja - Sri Anugrah Natalina (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
Shariâ€™ah mutual funds has its own charm than other types of mutual funds. Shariâ€™ah mutual funds isÂ not limited only to Muslims as the general public, who are already seeing the benefits of investmentÂ that is based on the choice of sector and company specific criteria more promising and minimize risk.Â Islamic mutual funds are able to contribute the confidence of investors amounted to 3.31% in 2011, 4.31% inÂ 2012 and 3.79% in 2013. So the value of the confidence of investors on mutual fund products sharia to 2013 is stillÂ around 3-4% . As for growth on Islamic mutual funds into one of the capital market products showed an increaseÂ in value in 2012 amounted to 3.79% later in the year 2013 to 4.32%.Â Investment portfolio management works based framework (framework) for investment management whichÂ covers the planning, implementation, evaluation, and adjustment. In mutual funds, investment managersÂ responsible for investment activities, which includes the analysis and selection of investment types, and performÂ the necessary actions for the benefit of investors. Form of mutual fund performance measurement Shariâ€™ahÂ assessed net asset value (NAV) of the sub weekly. Showed a good performance rekasadana Shariâ€™ah when in aÂ period of return obtained is more positive.Â